Rethinking the Elements of Architectural Heritage: An Experience from Medina, Saudi Arabia - Ashour, Randah (Journal of History Culture and Art Research, 2020)
Rowshan is the projected latticework window, commonly found in façades of traditional dwellings in Medina. Due to functions that Rowshan provides, such as overlooking the surroundings with complete privacy and controlling natural ventilation and lighting in the dwelling, it achieved a widespread popularity in the traditional architecture of Medina, which gave the city its unique architectural identity. This article explored the public's attitudes, awareness, and concerns on the dwindling traditional Islamic identity in contemporary architecture in Medina as well as to understand their social demands and functional aspiration as possible window's end users. The self-completed questionnaire was conducted with the general public in Madinah between the 1st of February 2017 and the 15th of March 2017, using the online web-based service, Google Forms. The link of the survey was distributed via emails and smartphones apps, such as WhatsApp, to the participants who were expected to complete the 23 questions of the survey within 15-20 minutes. The majority of study participants were males (73.1%), Saudis (79.2%), 30-49 years old (57.3%), had university degree (54.7%), house owners (54%), living in a flat (54.9%) and had a monthly income of up to SAR 10,000 (£1900) (63%). The majority of people were severely concerned about the gradual erosion of the authentic architectural identity in contemporary architecture in Medina. Visual privacy, the functional performance, and aesthetic appearance were chosen by a remarkable proportion of participants of survey (24%), (22.9%), and (20.7%), respectively as the most important issues that determined their selection of window shading type. Rowshan, compared with contemporary windows, was more effective in covering home windows for achieving satisfying levels of aesthetic appearance, visual privacy, and daylight at homes compared with contemporary windows as people agreed. However, there are three major drawbacks that make using of the traditional form of Rowshan incompatible with contemporary Madani architecture. These are high cost, large number of Rowshan openings, and lack of craftsmen. The findings of the present study showed that Madani society was highly motivated and had a positive attitude toward using Rowshan in their homes.